2011
DOI: 10.1103/physrevb.84.014512
|View full text |Cite
|
Sign up to set email alerts
|

BCS-BEC crossover induced by a synthetic non-Abelian gauge field

Abstract: 5We investigate the ground state of interacting spin-1 2 fermions in 3D at a finite density (ρ ∼ k 3 F ) 6 in the presence of a uniform non-Abelian gauge field. The gauge field configuration (GFC) described 7 by a vector λ ≡ (λx, λy, λz), whose magnitude λ determines the gauge coupling strength, generates 8 a generalized Rashba spin-orbit interaction. For a weak attractive interaction in the singlet channel 9 described by a small negative scattering length (kF |as| 1), the ground state in the absence of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
245
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(254 citation statements)
references
References 19 publications
9
245
0
Order By: Relevance
“…Note Added: During preparing this paper, we became aware of three preprints, in which similar problem has been addressed [13][14][15]. For the overlap part, our results agree with each other.…”
supporting
confidence: 80%
“…Note Added: During preparing this paper, we became aware of three preprints, in which similar problem has been addressed [13][14][15]. For the overlap part, our results agree with each other.…”
supporting
confidence: 80%
“…Generalizing conventional BEC-BCS crossover mean-field theory to the case with SO coupling and equal population n ↑ = n ↓ , one can show that the system remains gapped for all k F a s , although there are triplet p-wave components 60,61,62,63 , and the pair wave function obtained from the mean-field theory finally approaches the wave function of two-body bound state (i.e. molecule wave function) 60,62 .…”
Section: Spin-orbit Coupled Fermi Gases Across a Feshbach Resonancementioning
confidence: 99%
“…During the last few years these topics have gained an increasing interest for ultracold atomic gases [4][5][6][7][8] which represent the systems simulating many condensed matter phenomena. Recent experimental progress in the spin-orbit coupling (SOC) of degenerate atomic gases [9][10][11][12][13] has stimulated the theoretical studies of diverse new phases due to the SOC [8,[14][15][16][17], such as emergence of the stripe phase in atomic Bose-Einstein condensates (BECs) [18][19][20][21][22], or formation of unconventional bound states [23][24][25][26] and topological superfluidity [27] for atomic fermions. It was demonstrated that for the spin-orbit (SO) coupled BECs, the half-vortex (meron) ground states may develop in harmonic traps [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%